International Commodity Taxation under Monopolistic Competition - Andreas Haufler; Michael Pflüger (Deutsches Institut für Wirtschaftsforschung (DIW), 2003)
We analyze non-cooperative commodity taxation in a two-country trade model characterized by monopolistic competition and international firm and capital mobility. In this setting, taxes in one country affect foreign welfare through the relocation of mobile firms and through changes in the rents accruing to capital owners. With consumption-based taxation, these fiscal externalities exactly offset each other and the non-cooperative tax equilibrium is Pareto efficient. With production-based taxation, however, there are additional externalities on the foreign tax base and the foreign price level which lead non-cooperative tax rates to exceed their Pareto efficient levels.
Keywords: H87; H21; F12; 330; tax competition; market imperfections; international trade; Verbrauchsteuer; Neue Aussenhandelstheorie; Ursprungslandprinzip; Nichtkooperatives Spiel; Steuerwettbewerb; Steuerwirkung; Pareto-Optimum; Theorie